Magnetically recyclable CoFe2O4 nanoparticles as stable and efficient catalysts for the synthesis of aryl thioethers via C–S coupling reactions. (18th November 2022) - Iraqui, Saddam; Rashid, Md. Harunar
Abstract : An odourless and ligand-free protocol for the synthesis of aryl thioethers via a CoFe2 O4 NP catalysed coupling reaction between benzyl halides and aryl halides in the presence of thiourea as a sulphur source is reported. Abstract : Aryl thioethers and their derivatives constitute an important class of organic compounds that play an important role in the synthesis of natural products, and pharmaceutically and biologically active molecules. Hence, the formation of C–S bonds is a very important process in organic synthesis. The cross-coupling reaction is one of the most popular and powerful tools for C–S bond formation. This study presents an odourless and ligand-free protocol for the synthesis of aryl thioethers via a CoFe2 O4 NP catalysed coupling reaction between benzyl halides and aryl halides in the presence of thiourea as a sulphur source. CoFe2 O4 NPs have been synthesized by a hydrothermal process at 180 °C in the absence of any added stabilizer. The synthesized CoFe2 O4 NPs are spherical with sizes varying from 7 to 15 nm and possess cubic structures. They exhibit ferromagnetic behaviour at room temperature while above the blocking temperature, T B, the material shows superparamagnetic behaviour. This behaviour makes the catalyst magnetically separable and reusable up to 7th cycle without much loss of their catalytic activity. The protocol can be expanded to a wide array of substituted aryl halides and substituted benzyl halides with moderate to excellent yields.